Mindfulness effects on postural control and attention - Cheong, Michelle Sara Mingrong (2014)
Mindfulness has been suggested to curb habitual tendencies such as postural control. As mindfulness is principled on attention, and attention is associated with the visual environment, mindfulness can also aid in withstanding visual environmental distractions. This study sought to test these hypotheses through observing mindfulness effects on postural control and attention. Thirty-nine female participants (age: M = 22.1 ± 0.90) were randomized into the mindfulness or control group, and before and after the manipulation, performed a two-leg postural balance task on a force plate whilst wearing an eye-tracker and watching a first-hand view of a 30s rollercoaster ride. Postural control and attention were assessed through maximum deviations (MaxD) of postural sway and eye movements respectively. The 2 (group: mindfulness and control) X 2 (time: pre-test and post-test) mixed ANOVA results showed that postural control improved significantly in the medial-lateral direction (p = 0.018), but insignificantly in the anterior-posterior direction (p = 0.18), when mindfulness and control groups were compared. In contrast, results pertaining to improvements in attention were insignificant in both the horizontal (p = 0.413) and vertical directions (p = 0.486) when both groups were compared. The study found mindfulness improved postural control, supporting the hypothesis that it can curb habitual tendencies, but the insignificant attention results suggested that mindfulness did not particularly help the participants withstand environmental distractions. This could however, have been due to experimental limitations, and this study should be replicated with larger sample sizes or different age groups and investigated further.